PENENTUAN KUALITAS AIR SUMUR BOR DI DAERAH MARANGKAYU KABUPATEN KUTAI KARTANEGARA - Yessy Parasamya Anggraini; Marlon Ivanhoe Aipassa; Aman S. Panggabean (JURNAL KIMIA MULAWARMAN, 2020)
The research about determination of the quality of drilled water wells in the area of Marangkayu, Kutai Kertanegara district has been conducted. The quality of the wellbore produced can be done by determining the number of several important parameters of the wellbore’s groundwater quality of groundwater wells produced by the Director General of SDA Ministry of PUPR and community groundwater wells in the coastal area of Marangkayu, whether it meets the requirements of the Republic of Indonesia Minister of Health Regulation No. 32/2017 concerning Environmental Health Standard Quality Standards and Water Health Requirements for Sanitation Hygiene. The results of the research showed that the government drilled water and community well drilled water met the quality standards in accordance with the Republic of Indonesia Ministerial Regulation No. 32/2017, except for E. Coli and Total Coliform contents are quite high, exceeding the quality standards of water sample inspection results.